Budesonide and the Gluten Containing Elimination Diet as Treatments for Non-responsive Celiac Disease in Children. Issue 5 (22nd August 2022) - Ali Ibrahim, Awab; Kenyon, Victoria; Fasano, Alessio; Leonard, Maureen M.
Abstract : Objectives: Non-responsive celiac disease (NRCD) is defined as patients having persistent symptoms and enteropathy (Marsh 3 histology) suggestive of active celiac disease (CeD), after following a gluten-free diet (GFD) for at least 12 months. NRCD is suggested to affect 15% of children with CeD but data are limited and there is no research to date describing treatment of children with this condition. The aim of this study was to describe our center's approach to identifying and treating NRCD with budesonide and the Gluten Containing Elimination Diet (GCED). Methods: We performed a retrospective, single center analysis over a 5-year period of patients with CD less than 18 years of age (inclusive) who underwent treatment for persistent symptoms and enteropathy despite following a GFD. Results: We identified 22 patients with NRCD. Thirteen were treated with the GCED for 3 months with 46% achieving both histological and symptomatic resolution. Nine patients were treated with budesonide (6–9 mg), with 89% achieving both symptomatic and histologic resolution after a median 3-month treatment course. Further, 67% of patients who responded to the GCED and 100% of patients who responded to budesonide remained in remission for at least 6 months following treatment transition back to exclusive GFD. Conclusions: The GCED and budesonide can provide benefit for NRCD. Most patients with NRCD can return to a GFD after 3 months of treatment.